2001
DOI: 10.1021/ma010270h
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior and Thermal Properties for Binary Blends of Compositionally Fractionated Poly(3-hydroxybutyrate-co-3-hydroxypropionate)s with Different Comonomer Composition

Abstract: Bacterially synthesized poly(3-hydroxybutyrate-co-3-hydroxypropionate) [P(3HB-co-3HP)] samples were compositionally fractionated using solvent/nonsolvent fractionation techniques. Binary blends between these compositionally fractionated P(3HB-co-3HP) samples, with much narrower comonomer compositional distribution, were prepared, and their thermal and crystallization behavior were studied using differential scanning calorimeter (DSC) and polarized optical microscopy. It was found that, in the amorphous phase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…The principal components of P(3HB‐ co ‐3MP) pH6.5 and P(3HB‐ co ‐3MP) pH7.0 were the copolyesters with more than 60 mol‐% 3MP unit content and that with about 20 mol‐%, respectively. In other words, an amorphous area of 3HB‐unit rich P(3HB‐ co ‐3MP) and that of 3MP‐unit rich P(3HB‐ co ‐3MP) are immiscible in each other 8,13,30,31. It was known that the bacterially synthesized 3HB‐rich P(3HB‐ co ‐3MP) took the crystalline structure of 3HB type, and the 3MP‐rich P(3HB‐ co ‐3MP) took the crystalline structure of 3MP type 25.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal components of P(3HB‐ co ‐3MP) pH6.5 and P(3HB‐ co ‐3MP) pH7.0 were the copolyesters with more than 60 mol‐% 3MP unit content and that with about 20 mol‐%, respectively. In other words, an amorphous area of 3HB‐unit rich P(3HB‐ co ‐3MP) and that of 3MP‐unit rich P(3HB‐ co ‐3MP) are immiscible in each other 8,13,30,31. It was known that the bacterially synthesized 3HB‐rich P(3HB‐ co ‐3MP) took the crystalline structure of 3HB type, and the 3MP‐rich P(3HB‐ co ‐3MP) took the crystalline structure of 3MP type 25.…”
Section: Resultsmentioning
confidence: 99%
“…The comonomer unit which was different from the other comonomer unit composing the crystalline phase might be excluded from the crystalline phase. It was suggested that the character in an amorphous area of original polymer had been decided by the difference of the crystalline type 13,15,30,31…”
Section: Resultsmentioning
confidence: 99%
“…Na et al have also investigated the physical behavior and thermal properties of the blends between fractionated P(3HB‐ co ‐3HP)s 33. The blend is miscible in the amorphous phase when the difference in 3HP‐unit content between two copolyesters is less than 30–40 mol‐%.…”
Section: Blends Of Fractionated Copolymersmentioning
confidence: 99%
“…So and hard segment crystallization and phase separation can be estimated from thermal transitions such as glass transition temperature, melting temperature, and crystallization temperature. [37][38][39] Our results indicate the poor miscibility of PLA and PLAE. In general, with an increased PLAE content, the T g-PLAE tends to shi to a higher temperature while T g-PLA is slightly lowered.…”
Section: Synthesis Of the Plag And Plaementioning
confidence: 71%